2021
DOI: 10.3390/nu13093213
|View full text |Cite
|
Sign up to set email alerts
|

Association of Differences in Dietary Behaviours and Lifestyle with Self-Reported Weight Gain during the COVID-19 Lockdown in a University Community from Chile: A Cross-Sectional Study

Abstract: Domiciliary confinement of people is one of the main strategies to limit the impact of COVID-19. Lockdowns have led to changes in lifestyle, emotional health, and eating habits. We aimed to evaluate the association of differences in dietary behaviours and lifestyle with self-reported weight gain during the COVID-19 lockdown in Chile. In this cross-sectional analytical study, five previously validated surveys were condensed into a single 86-item online questionnaire. The survey was sent to 1000 potential partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 42 publications
2
17
0
3
Order By: Relevance
“…Similar studies in Ibero-American countries indicated a weight gain in 48.6% of participants during social isolation [ 20 ]. Moreover, a study with 639 Chilean participants indicated an average weight gain of 1.99 kg [ 21 ]. These similar results may be because the population of this region of the world has similar eating habits, as was demonstrated in a representative sample of the urban population of Latin America [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar studies in Ibero-American countries indicated a weight gain in 48.6% of participants during social isolation [ 20 ]. Moreover, a study with 639 Chilean participants indicated an average weight gain of 1.99 kg [ 21 ]. These similar results may be because the population of this region of the world has similar eating habits, as was demonstrated in a representative sample of the urban population of Latin America [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies in different Latin American countries such as Argentina, Mexico, and Brazil showed high proportions of their population with overweight and obesity during the period of social isolation [ 20 ]. Additionally, in another study with Chilean adults, an increase of 0.7 units of BMI was reported [ 21 ]. The population of these countries presented a low overall diet quality score and low dietary diversity [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in other countries have also investigated eating behaviours during the COVID-19 pandemic, reaching conflicting results [24][25][26][27][28]. However, the way negative emotions impact food consumption and their possible impact on body weight has only been assessed in an adolescent population [29].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the potential for long-lasting effects including PTSD warrants the need for ongoing psychological support which may require physical, pharmacological and psychological interventions [ 35 ]. Current medical practices may also need to be adapted to facilitate healthcare delivery peripherally, such as via telemedicine approaches and the establishment of suitable support groups, and a potential requirement to adopt lifestyle changes that may arise from domiciliary confinement [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%